Fluorescence Molecular Imaging of Small Animal Tumor Models - Graves, E. E.; Weissleder, R.; Ntziachristos, V. (Current Molecular Medicine, 2004)
In vivo imaging of molecular events in small animals has great potential to impact basic science and drug development. For this reason, several imaging technologies have been adapted to small animal research, including X-ray, magnetic resonance, and radioisotope imaging. Despite this plethora of visualization techniques, fluorescence imaging is emerging as an important alternative because of its operational simplicity, safety, and cost-effectiveness. Fluorescence imaging has recently become particularly interesting because of advances in fluorescent probe technology, including targeted fluorochromes as well as fluorescent “switches” sensitive to specific biochemical events. While past biological investigations using fluorescence have focused on microscopic examination of ex vivo, in vitro, or intravital specimens, techniques for macroscopic fluorescence imaging are now emerging for in vivo molecular imaging applications. This review illuminates fluorescence imaging technologies that hold promise for small animal imaging. In particular we focus on planar illumination techniques, also known as Fluorescence Reflectance Imaging (FRI), and discuss its performance and current use. We then discuss fluorescence molecular tomography (FMT), an evolving technique for quantitative three-dimensional imaging of fluorescence in vivo. This technique offers the promise of non-invasively quantifying and visualizing specific molecular activity in living subjects in three dimensions.
Keywords: fluorescence